The chemistry of first row transition metal-oxo clusters - Smith, M. A. (2021)
Transition metal-oxo clusters have been widely studied in recent years due, in part, to their varied redox behaviour and magnetic properties. In particular, the design and fabrication of new first-row transition metal-oxo clusters is a significant target in the fields of catalysis and molecular magnetism. The properties of the systems change significantly across the periodic table, with high stability and relative inertness associated with early transition metal-oxo compounds contrasting with the highly reactive oxidizing chemistry of compounds based on later transition metals. This critical review outlines the chemistry of the oxo-clusters of the first-row transition metals, illustrating the synthetic pathways, structural features and fundamental chemistry of these systems.